2010
DOI: 10.1007/s13213-010-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biosynthesis in Cunninghamella bainieri 2A1 in N-limited and N-excess media

Abstract: Lipid biosynthesis and fatty acids composition of oleaginous zygomycetes, namely Cunninghamella bainieri 2A1, cultured in media with excess or limited nitrogen were quantitatively determined at different times of culture growth. Accumulation of lipids occurred even when the activity of NAD+-ICDH (β-Nicotinamide adenine dinucleotide-isocitrate dehydrogenase) was still detectable in both media. In C. bainieri 2A1, under nitrogen limitation, the ratio of lipids was around 35%, whereas in nitrogen excess medium (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Previous studies have revealed that a high amount of lipid could be accumulated by the fungal species of Cunninghamella depending on the fermentation methods and culture conditions (Fakas et al, 2007, Fakas et al, 2009, Somashekar et al, 2003). Similar studies have shown that a high lipid accumulation is attained by Cunninghamella bainieri 2A1 in the submerged batch culture (Taha et al, 2010). It is well known that C. bainieri 2A1 is capable of producing up to 30% lipid (g/g biomass) which contains 10–15% GLA.…”
Section: Introductionsupporting
confidence: 61%
“…Previous studies have revealed that a high amount of lipid could be accumulated by the fungal species of Cunninghamella depending on the fermentation methods and culture conditions (Fakas et al, 2007, Fakas et al, 2009, Somashekar et al, 2003). Similar studies have shown that a high lipid accumulation is attained by Cunninghamella bainieri 2A1 in the submerged batch culture (Taha et al, 2010). It is well known that C. bainieri 2A1 is capable of producing up to 30% lipid (g/g biomass) which contains 10–15% GLA.…”
Section: Introductionsupporting
confidence: 61%
“…depending on the fermentation methods and culture conditions [ 5 , 6 ]. Similar studies have shown that a high lipid accumulation is attained by Cunninghamella bainieri 2A1 in shake flask culture [ 7 ]. It is worth noticing that microbial lipids are mostly comprised of triacylglycerols (TAGs) with the lower quantities of free fatty acids, natural lipids (monoacylglycerols, diacylglycerols, and steryl-esters), sterols, and polar fractions such as phospholipids, sphingolipids, and glycolipids.…”
Section: Introductionsupporting
confidence: 52%
“…It has been reported that several species of Cunninghamella, such as C. elegans (Čertík et al 1993), C. echinulata (Fakas et al 2006) and C. bainieri (Taha et al 2010), can accumulate lipids in their cells, and these species have consequently been designated as oleaginous (Certik et al 1999). According to this definition, C. bigelovii would be an oleaginous fungus.…”
Section: Discussionmentioning
confidence: 99%